PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI DI DINAS PETERNAKAN DAN PERTANIAN KABUPATEN KUTAI TIMUR - Ludia Rura Fl. Sudiran (ADMINISTRASI PUBLIK, 2017)
This study aims to find the effect of job satisfaction on employee commitment in the Livestock and Agriculture East Kutai, therefore the researchers to formulate hypotheses